The effect of price fairness on negative consumption emotion of airline passengers - Abdulmalek Omar Mosleh, Anhar; Maulan, Suharni; Haque, A. K. M. Ahasanul (Southern Academic Publisher, 2023)
Pricing remains a crucial phenomenon for companies operating in a competitive environment. When it comes to selecting a service, price often tends to be a significant consideration for most customers. The aim of this study is to examine the relationship between price fairness and negative consumption emotion of passengers towards airline services. The respondents of this study are passengers who have travelled within one year from /to or within Malaysia using full-service airlines or low-cost carriers. The data was collected using online survey. Data analysis was done using SPSS and PLS-SEM software where 197 responses were suitable for analysis. The findings show that price fairness has negative relationship with negative consumption emotion. This indicates that price fairness plays an important role in reducing negative emotion of the passengers regardless of the situation. The findings of this study can assist airline managers towards understanding the negative impact of negative emotions, and thus provide managers with insights on balancing between fair price and good service